Optimization of multipulse converters with delta and Y-differential connections - Oliveira, Priscila Da Silva [UNESP]; Mendes de Seixas, Falcondes J. [UNESP]; Fernandes, Rodolfo Castanho [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2009)
This work presents a study regarding the optimization of multipulse converters. A general expression for the connection (Δ or Y) for both 12 and 18-pulses is obtained and describes the output voltages on the secondary windings, depending on the voltage reference from the primary. These generalized expressions allows choosing different ratios between input and output voltages and as result an optimum operation point for the converter can be calculated. Considering Δ-connected converters the optimum point occurs when the magnetic core of the autotransformer processes 18% and 17% of the output power for 12 and 18-pulses, respectively. For Y-connected converters the optimum point occurs when the kVA rating is 13% and 18% for 12 and 18-pulses, respectively. Based on these results magnetic elements can be calculated and designed leading to a great weight and volume reduction and also to lower costs and losses. Finally an analysis is made to improve the kVA rating of the transformers for 12 and 18 pulses converters. © 2009 IEEE.
Keywords: Autotransformer; Differential connection; Multipulse converter; Reduction of harmonics; 18-pulse; General expression; Input and outputs; Lower cost; Magnetic elements; Multi-pulse converters; Optimum operations; Output power; Output voltages; Secondary windings; Voltage reference; Volume reductions; Magnetic circuits; Power electronics